Prevalence and Identification of Bacterial Species Causing Antibiotic-Resistant Otitis Media in Zawia City, Libya, and Identification of Associated Risk Factors - Mabroukah Khalleefah,; Najat Mansour,; Ali Milad,; Suad Diab,; Lubna Elbishti,; Himedah Fheel Alboom,; Khaled Aburas,; Najat Gooma, (AlQalam Journal of Medical and Applied Sciences, 2026)
Otitis media (OM) is a common infection of the middle ear, often leading to multiple visits to healthcare centers due to complications such as hearing loss and other serious infections, particularly in developing countries. Bacteria are the most common causative agents of OM. This study aimed to identify and differentiate the bacterial species causing OM in Zawia city and to determine their antimicrobial susceptibility patterns. The study was conducted at Al-Zawia Medical Laboratory from January 1, 2024, to June 1, 2024. A total of 200 individuals were included, of which 157 (78.5%) were diagnosed with middle ear infection. The results indicated a high incidence of bacterial OM in the 41-50 age group, with females being more affected than males in this group. Conversely, the 11-20 age group showed a higher infection rate in males. Of the 157 bacterial pathogens isolated, 67 (42.68%) were from male patients and 90 (57.32%) were from female patients. The most prevalent isolates were Staphylococcus aureus (16.5%), Pseudomonas sp. (14%), and Klebsiella sp. (9%). Antimicrobial susceptibility testing showed that Gentamycin exhibited high sensitivity against most isolates. The high rate of bacterial resistance to most tested antibiotics highlights the need to prescribe antibiotics based on local antibiogram data and bacterial sensitivity. Bacterial pathogens were identified phenotypically and culturally, and a significant variation in their susceptibility to antibiotics was observed.